Identification of Secreted O-Mannosylated Proteins From BCG and Characterization of Immunodominant Antigens BCG_0470 and BCG_0980 - Deng, Guoying; Zhang, Wenli; Ji, Na; Zhai, Yunpeng; Shi, Xiaoxia; Liu, Xin; Yang, Shufeng (Frontiers in Microbiology, 2020)
Glycoproteins have been characterized as vaccine candidates and diagnostic biomarkers in bacteria. However, they are poorly understood in bacille Calmette-Guérin (BCG), a non-pathogenic workbench of Mycobacterium tuberculosis (M. tuberculosis). To reveal the roles of secretory O-mannosylated glycoproteins in BCG, we conducted a ConA lectin-affinity chromatography and Mass Spectra analysis to identify the O-mannosylated proteins in the culture filtration of BCG. Subsequent screening of antigens was performed using poly-clonal antibodies obtained from BCG-immunized mouse. Consequently, fifteen endogenous O-mannosylated proteins were identified. Of 15, BCG_0470 and BCG_0980 (PstS3) were revealed as the immunodominant antigens in this study. To further characterize the identified antigens, we constructed their recombinant proteins expressed in Mycobacterium smegmatis (M. smegmatis) and E.coli. Using recombinant antigens to boost BCG primed-mice, we found more DTH responses in vivo and stronger Th1 responses including IFN- ɣ and TNF-ɑ, and higher level antigenic-IgG in vitro occurred. Thereby, our results showed that the mannosylated proteins of BCG_0470 and BCG_0980 could amplify the immune responses induced by BCG, and the oligosacchride chains were part of antigen for BCG_0470. Thus, our results revealed that the oligosacchride chains containing mannose were the antigenic determinants of glycoproteins. This study provides an innovative insight into vaccine optimizations and designs.